"Frozen" pressure effect in GGAG:Ce3+ white light emitting nanoceramics. Issue 17 (1st December 2019) - Głuchowski, Paweł; Tomala, Robert; Kowalski, Robert; Ignatenko, Oleg; Witkowski, Marcin E.; Drozdowski, Winicjusz; Stręk, Wiesław; Ryba-Romanowski, Witold; Solarz, Piotr
Abstract: Nanocrystalline powders of Ce 3+ doped Gd3 Ga3 Al2 O12 (GGAG) with the size of tens nanometers were prepared using modified Pechini method. Low Temperature High Pressure sintering method was used for the fabrication of the translucent nanoceramics using as starting materials nanocrystalline GGAG:Ce 3+ powders. For growth of GGAG:Ce single crystal the Czochralski method was utilized. XRD measurement was used in order to characterize the grain size of the GGAG:Ce 3+ nanostructures. Excitation and emission and luminescence decays measurements were done to observe impact of the grain size and applied pressure on the spectroscopic properties of crystallites and ceramics. It was observed that for the smallest grains both spectra are significantly changed. The spectroscopic properties of the nanopowders were compared to the GGAG:Ce 3+ ceramics made from them as well as to the single crystal. It was found that is possible to modify permanently the crystal field in the nanocrystals by applying the pressure during sintering.